Pendidikan Akidah dalam Al-Qur’an (QS. Al-Ikhlas, QS. Al-Fatihah, dan QS. Al-Baqarah:255) - Ghina Sofia Mahfuzaha; Mahyuddin Barni (CV. ITTC INDONESIA, 2025)
This study examines the values of aqidah education contained in three key Qur’anic passages: Surah Al-Ikhlas, Surah Al-Fatihah, and Surah Al-Baqarah verse 255 (Ayat al-Kursi). Aqidah serves as the fundamental basis of a Muslim’s character and religious integrity; therefore, understanding Qur’anic guidance on correct belief is essential. This research aims to describe the core theological principles presented in the three verses and to analyze their relevance for strengthening Islamic faith in contemporary life. Using a qualitative descriptive method through textual and thematic analysis, this study explores the concept of pure monotheism in Surah Al-Ikhlas, the principles of servitude, gratitude, reliance, and guidance in Surah Al-Fatihah, and the affirmation of Allah’s sovereignty, eternal power, and protection in Ayat al-Kursi. The findings indicate that these three verses collectively provide a comprehensive framework for aqidah education that shapes a firm, sincere, and God-centered personality. They also demonstrate that internalizing the Qur’anic values of monotheism contributes significantly to protecting Muslims from deviant ideologies, cultivating spiritual resilience, and strengthening religious commitment in everyday life. Thus, Qur’anic-based aqidah education remains essential for developing faithful, morally grounded, and spiritually aware individuals.